2016
DOI: 10.18869/acadpub.ijmt.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Semi-Active Tunes Mass Damper Application in Suppressing Seismic-Induced Vibration of an Existing Jacket Platform

Abstract: In this study, mass, stiffness and damping matrices of the Nosrat jacket; located in Persian Gulf; equipped with Semi Active Tuned Mass Damper (SATMD) system have been derived after modeling the structure in SACS software. Owing to huge number of the degrees of freedom in the model, computation of on-line control of SATMD was time consuming. For this purpose, the size of the model was reduced in the finite time and frequency intervals by programming in MATLAB software. The SATMD utilized in this study, contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Semi-active control scheme [15,16] is an excellent approach for the vibration control as these controllers utilized the benefits of both passive and active control system. The major control algorithms, clipped optimal control algorithm [14], Bang-Bang control algorithm [17], LQG algorithm [30], linear quadratic control algorithm [18] and non-resonance control algorithm [19], are used for implementation of semi-active control schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-active control scheme [15,16] is an excellent approach for the vibration control as these controllers utilized the benefits of both passive and active control system. The major control algorithms, clipped optimal control algorithm [14], Bang-Bang control algorithm [17], LQG algorithm [30], linear quadratic control algorithm [18] and non-resonance control algorithm [19], are used for implementation of semi-active control schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the structural stabilization systems are either mounted on or embedded inside the main structure. This type of Tuned Mass Dampers (TMD) are designed to mechanically damp the vibration either passively, actively or even semi-actively [14][15][16][17]. The efficiency of these systems is associated with their mass, stiffness and damping coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are often costly, energy-consuming and complicated [6,12]. Moreover, in previous works the proposed TMD stabilization mechanisms are either mounted on or embedded inside the main structure and have no contact with the surrounding water [14][15][16][17]. The proposed system in this study, however, provides a stabilized buoy, as a result of which, the sensors mounted on it might no longer require individual mechanical stabilization systems.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that MR dampers efficiently help in reducing displacement & acceleration. From the results of time history analysis of the deck platform with Semi Active Tuned Damper reported in the literature [4] showed that Semi Active Tuned Damper can dramatically reduce the acceleration and displacement of the platform. The nonlinear response of a fixed deck platform has been studied under wave loading [5] and it was found that it is crucial to decrease the overall response of an offshore structure subjected to environment loads.…”
Section: Introductionmentioning
confidence: 99%